Association of Hormonal Contraceptives with Depression among Women in Reproductive Age Groups: A Cross-Sectional Analytic Study - Sadia Sultan; MD. Abu Bashar; Rahma M. Bazhair; Doaa O. Abdurahman; Renad A. Alrehaili; Meimouna E. Ennahoui; Yasmeen S. Alsulaiman; Seba D. Alamri; Elgawhara F. A. Mohamed (Obstetrics and Gynecology International)
Introduction. Hormonal contraceptives (HCs) are used for birth control, menstrual disturbances, and premenopausal syndrome. Most women stop using hormonal contraceptives due to changes in their mood. The evidence regarding the association of hormonal contraception with depression shows mixed results. Therefore, we aim to establish the association between the use of hormonal contraception and depressive symptoms. Methods. A cross-sectional study was conducted on 326 women of the reproductive age group (15–49 years) attending the family planning unit of the obstetrics and gynecology department of a medical college in Saudi Arabia. Their sociodemographic and medical details along with the current use of any contraceptives (hormonal, nonhormonal, or not using any) with duration were collected. Beck depression inventory-II (BDI-II) was applied to the women to assess for depression along with its severity, and a BDI score of >16 was taken to denote clinical depression. Women were stratified by type of contraceptive used, and its association with depression category was assessed. Results. A total of 326 consenting eligible women in the age group of 15–49 years were enrolled in the study of which 165 (50.6%) were currently using a hormonal contraceptive and 49 (15.0%) were using a nonhormonal contraceptive and the rest 112 (34.4%) were not using any contraceptives. There was no significant difference in the mean BDI scores (p=0.79) and degrees of depression (p=0.06) between the HC users and HC nonusers. However, individual symptoms of depression such as sadness (p=0.01), reduced libido (p=0.0002), feelings of pessimism (p=0.02), and failure (p=0.003) were found to be significantly higher in the HC users than non-HC users. Conclusion. We conclude that there was no significant difference in mean depression scores between groups. However, a few individual symptoms of depression were high in HC users suggesting depression as a potential side effect of hormonal contraceptive use.